Ventilation Onset Prior to Umbilical Cord Clamping (Physiological-Based Cord Clamping) Improves Systemic and Cerebral Oxygenation in Preterm Lambs - Polglase, Graeme R. (PLoS One, 2015)
BACKGROUND: As measurement of arterial oxygen saturation (SpO(2)) is common in the delivery room, target SpO(2) ranges allow clinicians to titrate oxygen therapy for preterm infants in order to achieve saturation levels similar to those seen in normal term infants in the first minutes of life. However, the influence of the onset of ventilation and the timing of cord clamping on systemic and cerebral oxygenation is not known. AIM: We investigated whether the initiation of ventilation, prior to, or after umbilical cord clamping, altered systemic and cerebral oxygenation in preterm lambs. METHODS: Systemic and cerebral blood-flows, pressures and peripheral SpO(2) and regional cerebral tissue oxygenation (SctO(2)) were measured continuously in apnoeic preterm lambs (126±1 day gestation). Positive pressure ventilation was initiated either 1) prior to umbilical cord clamping, or 2) after umbilical cord clamping. Lambs were monitored intensively prior to intervention, and for 10 minutes following umbilical cord clamping. RESULTS: Clamping the umbilical cord prior to ventilation resulted in a rapid decrease in SpO(2) and SctO(2), and an increase in arterial pressure, cerebral blood flow and cerebral oxygen extraction. Ventilation restored oxygenation and haemodynamics by 5–6 minutes. No such disturbances in peripheral or cerebral oxygenation and haemodynamics were observed when ventilation was initiated prior to cord clamping. CONCLUSION: The establishment of ventilation prior to umbilical cord clamping facilitated a smooth transition to systemic and cerebral oxygenation following birth. SpO(2) nomograms may need to be re-evaluated to reflect physiological management of preterm infants in the delivery room.